Facilitated Versus Self-Directed Educational Modalities in Palliative Care Training: A Randomized Controlled Trial of the CAPACITI Intervention - Midori Matthew; Daryl Bainbridge; Jeff Myers; Oren Levine; Leah Steinberg; Nadia Incardona; Samantha Winemaker; Kathy Kortes-Miller; Kelli Stajduhar; Frances Kilbertus; Jose Pereira; Hsien Seow (Palliative Medicine Reports)
Background: Community Access to Palliative Care via Interprofessional Teams Improvement (CAPACITI) is a virtual educational program designed to support primary care providers in delivering a palliative approach to care. This study evaluated whether expert-facilitated sessions result in greater self-rated competency than a self-directed format across three CAPACITI modules: Identification and Assessment, Communication, and Ongoing Management. Methods: We conducted a randomized controlled trial where 566 interprofessional primary care team members were randomized to facilitated or self-directed delivery of the CAPACITI program. Participants completed two validated surveys at baseline and after each module: the End-of-Life Professional Caregiver Survey and the CAPACITI Competencies survey. These assessed self-rated comfort and competency in providing palliative care. Results: Of the 566 participants randomized, 378 completed Module 1, and 270 and 192 completed Modules 2 and 3, respectively. Participants in both study arms demonstrated significant improvements in self-assessed comfort and competency following each module. No significant differences were observed between the facilitated and self-directed groups across either survey instrument. Conclusion: Participants in both the facilitated and self-directed study arms reported significant increases in self-rated comfort and competency in providing a palliative approach to care. CAPACITI demonstrates that a relatively large, intensive, and feasible training program can be implemented virtually across diverse care settings. These results support the broader application of structured, scalable educational interventions in primary care, particularly those grounded in practical content and adult learning principles. Trial registration number: ClinicalTrials.gov NCT05120154. Date registered: Oct 15, 2021. The authors affirm that this trial was registered prior to enrolling any participants.